Effects of Game-Based and Exploratory Strategies on Science Content Knowledge and Science Processing Skills of Pre-Primary Children in Akinyele, Oyo State - Idowu Oluyemisi Majebi; Yewande Gbemisola Akin (Universitas Negeri Semarang, 2023)
Strategies that give room for children’s active involvement during teaching activities have a high probability of bringing about all-round development and learning in them in all areas, especially science. Pre-primary children have less exposure to science related activities possibly because of the strategy adopted during teaching activities, which might likely affect their acquisition of science knowledge and processing skills later. Hence, this study adopted game-based and exploratory strategies to engage the pre-primary children in some concepts in pre-primary science. The purposive random sampling technique was used to select three pre-primary public schools in one local government. Two were assigned to experimental groups of game-based and exploratory strategies respectively while one was assigned to the control group. 59 pre-primary children participated. Pre-test-post-test control group quasi-experimental design was adopted. Six research questions were answered and three hypotheses were tested at a 0.05 level of significance. Five research instruments were used to collect data. Data were analysed using analysis of covariance (ANCOVA) and Scheffe posthoc test. Results showed significant effects of treatments on pre-primary children’s science knowledge and processing skills. There were mean gains of 2.0 (game-based); 1.63 (explorative) and 0.55 (conventional) points in science knowledge. There were also mean gains of 19.45 (game-based); 20.58 (exploratory) and 10.55 (conventional) points in the processing skills of pre-primary children. The exploratory strategy was more effective than the game based on science process skills and knowledge. The conventional strategy was less effective than the two. Game-based and exploratory strategies were recommended for pre-primary teachers in teaching science concepts. Keywords: Game-based and exploratory strategies, Science knowledge, Science process skills